After the Killing of Atatiana Jefferson: Black Stakeholder Experiences Within a Municipal Listening Structure. (September 2022) - O'Neil, Julie; English, Ashley E.; Lambiase, Jacqueline
Starting with a public relations pioneer's maxim to "listen to stakeholders, " many contemporary scholars have emphasized listening as the key to the inclusion of marginalized communities. Based on 25 in-depth interviews including 19 Black residents of Fort Worth, this study amplifies the voices of Black community members after the killing of Atatiana Jefferson in her home by a White police officer. Their perceptions of systemic racism within the city's listening processes and their recognition of pseudo-listening and non-action provide an understanding of and suggestions for how the city government can facilitate equitable engagement.